Kepemimpinan Perempuan dalam Pengelolaan Budaya Pesantren di Dayah Darul Aman Tungkop Aceh Besar - Mardhiah, Ainul (Pencerah, 2023)
A leader is a person who sets goals, motivates and takes action on his subordinates. Leadership is the characteristic of a leader in assuming formal moral and legal responsibility for all the implementation of authority that has been delegated to the people he leads. Dayah Darul Aman or this foundation is led by women with management of Islamic boarding school culture based on Dayah education and also school education. The purpose of this research is to find out the management of Islamic boarding School culture implemented by female leadership in Dayah Darul Aman Tungkop Aceh Besar. The method used in this research is descriptive qualitative research. The research subjects were Islamic boarding school leaders, teachers and students. Data collection techniques use observation, interviews and documentation. The results of this research indicate that the leadership applies management functions, namely planning, organizing, actuating, controlling and evaluating in Islamic boarding school leaders in Dayah Darul Aman Tungkop Aceh Besar.